Effective capacity analysis of full-duplex-cooperative non-orthogonal multiple access systems - Huu Quy Tran; Samarendra Nath Sur (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2024)
This study explores a dual-user full-duplex cooperative non-orthogonal multiple access (FD-CNOMA) network, presenting closed-form expressions for the outage probability (OP) and effective capacity (EC) of both users. The analytical results indicate that an increased signal-to-noise ratio (SNR) corresponds to a reduced OP and heightened EC, signifying enhanced communication quality. We analyze the OP and EC under two cases: R1=2R2 and R1=R2. Our analytical expressions reveal that both θ and ρ significantly impact the effective capacities. To validate these analytical findings, Monte Carlo simulations are performed, demonstrating alignment between theoretical insights and practical outcomes. The results underscore the critical role of SNR in influencing network performance, providing valuable insights into optimizing communication quality in FD-CNOMA systems.